Mechanical behavior of carbon fiber/epoxy filament wound laminates exposed to hygrothermal conditioning - Almeida, José Humberto S.; Souza, Samia D. B. [UNESP]; Botelho, Edson C. [UNESP]; Amico, Sandro C. (My University, 2015)
This work aims to evaluate the effect of hygrothermal conditioning on the tensile, in-plane shear and viscoelastic properties of carbon fiber/epoxy laminates (fiber volume fraction ≈ 70%). The flat unidirectional laminates were manufactured by filament winding process using a KUKA robot and the composites were cured under hot compression molding. The laminates were later exposed to hygrothermal conditioning. All composite samples were tested before and after environmental conditioning in a hygrothermal chamber. Elastic and strength tensile properties reduced for aged specimens, e.g. [0]4 sample presented a reduction of 18% in tensile strength and 8% in elastic modulus. Shear strength and modulus followed the same trend, and shear modulus reduced in about 38%. Tensile and shear post-test specimens presented accepted failure modes, since for instance, shear specimens failed at the gage section with delaminations.
Keywords: Advanced composites; Environmental effect; Filament winding; Mechanical performance